A hidden harvest from semi-arid forests: landscape-level livelihood contributions in Zagros, Iran. Issue 2 (3rd April 2019) - Mahdavi, Ali; Wunder, Sven; Mirzaeizadeh, Vahid; Omidi, Mehdi
ABSTRACT: In a forest-scarce country like Iran, the open semi-arid Zagros forests are the single-most important forest region, yet their contribution to rural livelihoods remains inadequately understood. Here our primary focus is on analyzing the quantitative contributions of these oak-pistachio tree savannas to rural household incomes in Malekshahi County, Ilam Province, considering both cash and subsistence sources, and direct as well as indirect incomes. Direct forest-extractive incomes prove to be comparatively small (6% of household incomes), and are dominated by foods (wild vegetables, pistachios, and fruits), fuels, and livestock feeds. However, forest incomes are egalitarian in distribution, and strategic in their nature: they keep one-fifth of households from falling below the poverty line. The poorest are thus also more forest- and firewood-reliant, but more surprisingly, so are specialized pastoralists. Moreover, indirect benefits in terms of forest inputs into agriculture are crucial: 20–25% of the crops are planted in tree savannas generating 7–9% of household incomes. All forests support goat and sheep grazing in the dry season as a vital refuge of vegetation resources, likely with an even higher value of household income (around 10%). Future research should look closer into those forest-farm linkages.